Analysis of the optical band positions for manganese (IV) ions in trigonal barium titanium hexafluoride and barium silicon hexafluoride crystals. Issue 8 (14th September 2018) - Li, Xiao-Wu; Mei, Yang; Liu, Hong-Gang; Zheng, Wen-Chen
Abstract: The optical band positions (or crystal field energy levels) of manganese (IV) ions in trigonal barium titanium hexafluoride and barium silicon hexafluoride crystals are computed from the full diagonalization (of energy matrix) method founded on the two-spin–orbit-parameter model which consists of the effects from both the spin–orbit parameters of d n ion and ligand ions. The computed results are in rational agreement with the experimental values. It is found that the large difference of first excited state splitting Δ E ( 2 E ) between the manganese (IV)-doped barium titanium hexafluoride and barium silicon hexafluoride crystals is owing mainly to the great difference of trigonal distortion between the fluorine octahedral clusters in the two host crystals.